Effects of Lactobacillus Strains as a Probiotic and a Hypolipidaemic Agent for Chickens - Ramasamy, Kalavathy (2003)
In recent years, there has been considerable interest in the beneficial effects of probiotics (direct-fed microbials, which include Lactobacillus) to modulate the lipid metabolism. However, the mechanism(s) involved remains unclear. A series of experiments was carried out to investigate the ability of 1 2 Lactobacillus strains to deconj ugate bile salts and to remove cholesterol in vitro, and to assess their potential as a pro biotic and as a hypolipidaemic agent for broilers and laying hens. Bile salt hydrolase (BSH) activity (resulting in bile salt deconjugation) of intestinal bacteria is closely linked to the lowering of cholesterol. The results of the in vitro studies showed that all the 1 2 Lactobacillus strains could deconjugate sodium glychocholate (GCA) and sodium taurocholate (TCA) bile salts, and all the strains, except L. fermentum I 24, had a higher affinity for GCA. However, only eight strains could deconjugate sodium taurodeoxycholate (TDCA). This indicates that the BSH of the Lactobacillus strains is substrate specific. The 1 2 Lactobacillus strains showed significant differences in their ability to reduce cholesterol from the growth medium (27 to 85 %) with or without bile salt, indicating that bile salt is not a prerequisite for the removal of cholesterol. Lactobacillus acidophilus I 1 6, L. crispatus I 1 2, L. brevis C 1 7 and I 2 1 1 , and L. Jermentum I 24 and I 25 removed cholesterol from the growth medium mainly through assimilation of cholesterol into the cells. On the other hand, L. brevis C 1 , C 1 0, I 23 and I 2 1 8, and L. Jermentum C 1 6 removed cholesterol through both assimilation and co-precipitation of deconjugated bile salt with cholesterol at low pH. The Lactobacillus strains assimilated more esterified than non-esterified cholesterol and the assimilated cholesterol was tightly bound to the cells. Cells grown in the presence of cholesterol were more resistant to lysis by sonication than when grown in its absence, suggesting a possible alteration of the cell wall or membrane by the assimilated cholesterol. Cholesterol removal by the Lactobacillus strains was also affected by Tween 80. The feeding trials showed that the supplementation of a mixture of the 1 2 Lactobacillus cultures (LC), as a probiotic for broilers, significantly improved growth equivalent to that provided by the antibiotic, oxytetracycline, but the feed conversion ratio was better in LC-fed broilers. The supplementation of LC also significantly lowered the total cholesterol, low density lipoprotein cholesterol and triglycerides of the serum; the cholesterol of the carcass and liver; abdominal fat deposition; and fat contents of the liver, muscle and carcass of broilers; but there was little effect on the fatty acid compositions of the liver, muscle and carcass. In laying hens, the supplementation of LC improved the feed efficiency and hen-day egg production during the early stage of the laying cycle, and increased egg weight and influenced a shift from small and medium to large and extra large eggs throughout the laying cycle. However, LC had very little effect on improving the fatty acid composition, and the cholesterol and total fat contents of eggs.